The night guest - McFarlane, Fiona, 1978- (New York : Faber and Faber, an affiliate of Farrar, Straus and Giroux, 2014)
"An elderly Australian woman lets a mysterious and possibly sinister caretaker into her beach-side home and into her life"--
Barbara Jefferis Award, joint winner, 2014.
Keywords: Widows -- Fiction; Caregivers -- Fiction; Caregivers; Widows; Australia -- Fiction; Australia; Australian; Thrillers (Fiction); Fiction; Suspense fiction